Influence of a bleaching agent on the color stability of indirect composite resins immersed in dyes - Dos Santos, Daniele M. [UNESP]; da Silva, Emily V. F. [UNESP]; de Caxias, Fernanda P. [UNESP]; Goiato, Marcelo C. [UNESP]; Mendonça, Juliani B. [UNESP]; Cetrangolo, Denis [UNESP] (MDPI, 2019)
This study aimed to evaluate the effect of a bleaching agent on the color of extrinsically pigmented indirect composite resins. Samples of five resins (Adoro, Resilab, Cristobal, Sinfony, Epricord) were manufactured and divided into five groups: red wine, coffee, orange juice, Coca-Cola, and artificial saliva (control). The stained samples were immersed in a 38% hydrogen peroxide solution for 30 min per week, over three weeks. Color readings were performed at the initial state (L0), after 21 days of dye immersion (∆E1, L1), and after 7 (∆E2, L2), 14 (∆E3, L3), and 21 days (∆E4, L4) of bleach immersion. Data were subjected to ANOVA and Tukey’s honestly significant difference (HSD) test (α = 0.05). The color alteration was greater in ∆E1, regardless of color solution, indicating extrinsic pigmentation. The Resilab group exhibited greater ∆E1 values than the other resins. The bleaching agent promoted bleaching action on the surfaces of the materials studied, removing the previously impregnated pigments.
Keywords: Bleaching agents; Color; Composite resins; Staining